Experimental analysis of the performance coefficients of the butterfly valves - Sandalcı, Mehmet (My University, 2009)
KELEBEK VANALARDA PERFORMANS KATSAYILARININ DENEYSEL OLARAK İNCELENMESİ Bu çalışmada, DN65 ve DN80 öçlülerindeki iki farklı vana, standart test metodu ANSI/ ISA-75.02-1996’ya uygun olarak test edilmiştir. Bu test farklı akış hızlarında (2, 3 and 4 m/ s) ve farklı açıklık açılarında (disk açılarında) (0, 10, 20, 30 and 40°) gerçekleştirilmiştir. 0° açıklık açısı tam açık vana konumu olarak kabul edilmiştir. Farklı açıklık açılarına tekabül eden akış alan yüzdeleri hesaplanmış, farklı akış hızlarında ve farklı vana açıklıklarındaki basınç kayıpları kaydedilmiştir. Deneysel veriler kullanılarak K ve Cv değerleri hesaplanmış ve K ve Cv değerlerini akış alan yüzdelerine bağlı fonksiyon şeklinde veren korelasyonlar geliştirilmiştir. Ölçüm belirsizliklerinin, performans katsayıları üzerindeki etkisini göstermek için belirsizlik analizi yapılmıştır. Sunulan korelasyonlar, iki farklı kelebek vananın performans katsayılarının belirlenmesinde etkin bir yöntem sağlar. Kayıp katsayısı, akışkanın, vanaya giriş hızından bağımsızdır. Fakat düşük akış alan yüzdelerinde vana çapına bağlıdır. Buna rağmen , or , şeklinde sunulan korelasyonlar, %65’ den daha büyük akış alan yüzdelerinde, iki farklı vana çapı için kullanılabilir. Debi katsayısı akışkan giriş hızından bağımsızdır fakat vana çapına bağımlıdır. DN65 ve DN80 ölçüsündeki vanalar için sunulan korelasyonlar; ve , akış alan yüzdeleri cinsinden debi katsayılarını verir. K ve Cv için verilen bu korelasyonlar, pratik kullanımlar için kabullenilir. Kelebek vana üreticileri ve tasarımcıları, farklı vana açıklık değerlerine göre, K ve Cv ‘ yi kolayca bulabilirler. Kelebek vana, Kayıp katsayısı, Debi katsayısı, Belirsizlik analizi

EXPERIMENTAL ANALYSIS OF THE PERFORMANCE COEFFICIENTS OF THE BUTTERFLY VALVES In the present work, two different butterfly valves, DN65 and DN80, were tested according to standard testing method ANSI/ ISA-75.02-1996. The tests were performed at different flow rates such as 2, 3 and 4 m/ s and at different valve opening angles such as 0, 10, 20, 30 and 40°. The opening angle 0° was considered as the fully open valve. The flow area percentages,  , were calculated for different valve openings as 100, 82.64, 65.80, 50 and 35.72% and pressure drops, ΔP, were recorded for different valve openings at different velocities. Using the experimental data the loss and flow coefficients, K and Cv, were calculated and correlations were developed to give K and Cv as a function of the flow area percentage, . Uncertainty analysis was performed to show the effect of the measurement uncertainties on the performance coefficients. The proposed correlations provide an effective way to determine the performance coefficients of two different sizes of butterfly valves. The loss coefficient is independent of the inlet velocity but it is dependent of the valve size at the lower flow area percentage. However, when flow area percentage is more than 65% the proposed correlations, or , can be used for two valve sizes. Flow coefficient is independent of the inlet velocity but it is dependent on the valve size. The proposed correlations giving the flow coefficients as functions of the flow area percentage are and for DN80 and DN65 valves, respectively. Correlations for K and Cv which are given are appropriate for practical use. Manufacturer or designer of butterfly valves can find easily the corresponding K and Cv values for different valve opening. Butterfly valve, Loss coefficient, Flow coefficient, Uncertainty analysis.
Keywords: Belirsizlik Analizi; Makine Mühendisliği